Degradation of polyethylene plastic bags and bottles using microorganisms isolated from soils of Morogoro, Tanzania - Nakei, Monica D.; Misinzo, Gerald; Tindwa, Hamisi; Semu, Ernest (Frontiers in Microbiology, 2022)
Plastics have low biodegradability and are persistent in the environment, becoming a major source of pollution. The study herein was conducted to identify microbial isolates from soils of Morogoro, Tanzania capable of biodegrading plastics. The isolation and enumeration of bacteria, fungi, and actinomycetes was done using nutrient, potato dextrose, and starch casein agar, respectively. The population of the microorganisms ranged from 1.60 x 104 to 1.57 x 105 CFU/g of soil. The capability of microbial isolates to biodegrade ground polyethylene (PE) bags and bottles was tested using Bushnell and Haas agar. Many isolates could degrade plastics as depicted by the diameters of clear zones around colonies ranging from 1.0 to 66 mm and 1.0 to 73.7 mm for ground PE bags and bottles, respectively. Some isolates showed significant (P ≤ 0.05) differences in the ability to degrade plastics. Among the bacteria, actinomycetes, and fungi, unsequenced bacterial and actinomycetal isolates B1 and A3 as well as Aspegillus sp. (F7) were the most efficient degraders of PE plastic bags. On the other hand, Bacillus cereus, Streptomyces rochei, and Phoma sp., were the most efficient PE plastic bottles degraders. In degrading both PE plastic bags, the diameter of clear zones, ranged from 21.7 to 47.5 mm for bacteria, 27.2 to 30.2 mm for actinomycetes and 30.2 to 61.1 mm for fungi. For the case of plastic bottles, the clear zones diameter ranged from and 19.3 to 33.6 mm for bacteria, 25.9 to 32.2 mm for actinomycetes and 33.3 to 66.3 mm for fungi. This retrospective study sheds light on our understanding and the need of the bioprospecting of agricultural soils, water bodies and landfills containing plastics wastes that could lead to identification of more efficient microbial species with ability to degrade plastics.